2022
DOI: 10.1177/02692155221136108
|View full text |Cite
|
Sign up to set email alerts
|

Myofascial release for the treatment of pain and dysfunction in patients with chronic mechanical neck pain: Systematic review and meta-analysis of randomised controlled trials

Abstract: Objective To explore the effects of myofascial release (MFR) on pain and dysfunction in individuals with chronic mechanical neck pain (MNP). Data sources PubMed, Embase, Medline, Wiley Online Library, Web of Science, CNKI, VIP, WanFang Data, and the Cochrane Library were searched until 12 September 2022. Review methods This study was registered in PROSPERO (CRD42022302485). Methodological quality was assessed using Cochrane risk of bias assessment, and the quality of the evidence followed the GRADE recommendat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…The findings of this study are consistent with previous research, [ 36 , 37 ] which also reported significant improvements in similar variables following similar interventions. The study conducted by Hashim et al (2020) revealed that both Post-Isometric Relaxation and Laser Therapy interventions demonstrated efficacy in decreasing pain pressure threshold and pain intensity among patients with muscle trigger point discomfort.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study are consistent with previous research, [ 36 , 37 ] which also reported significant improvements in similar variables following similar interventions. The study conducted by Hashim et al (2020) revealed that both Post-Isometric Relaxation and Laser Therapy interventions demonstrated efficacy in decreasing pain pressure threshold and pain intensity among patients with muscle trigger point discomfort.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, there have been increasing meta-analyses of the efectiveness of MFR intervention in various types of diseases, and the results from these meta-analyses are similar to our fndings [34][35][36][37][38]. Te studies indicate a positive role of myofascial release in alleviating symptoms related to low back pain [34,35], fbromyalgia [36], neck pain [37], and orthopedic conditions [38], such as pain relief, improvement in sleep quality, and disability levels. Headaches may have multiple triggering factors, such as medication overuse [11], alcohol [39,40], obstructive sleep apnea [41], and sleep disorders [42], but at the same time, myofascial mechanisms are likely closely linked to headaches.…”
Section: Discussionsupporting
confidence: 54%
“…In recent years, there have been increasing meta-analyses of the effectiveness of MFR intervention in various types of diseases, and the results from these meta-analyses are similar to our findings [ 34 38 ]. The studies indicate a positive role of myofascial release in alleviating symptoms related to low back pain [ 34 , 35 ], fibromyalgia [ 36 ], neck pain [ 37 ], and orthopedic conditions [ 38 ], such as pain relief, improvement in sleep quality, and disability levels.…”
Section: Discussionmentioning
confidence: 99%
“…We included 17 publications in this map covering 13 health conditions. 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 The literature flowchart ( Figure 1 ) summarizes results of the study selection process, and eAppendix 2 in Supplement 1 presents citations for all excluded reviews at full-text screening.…”
Section: Resultsmentioning
confidence: 99%
“…The total number of primary studies about massage therapy for pain in the included reviews ranged from 2 studies to 23 studies. There were 12 reviews that included fewer than 10 primary studies 4 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 23 and 5 reviews that included 10 to 25 studies about massage therapy for pain. 10 , 18 , 19 , 24 , 25 Of included reviews, 3 reviews were completed by the Cochrane Collaboration 4 , 19 , 23 and 2 reviews were completed by the AHRQ EPC program.…”
Section: Resultsmentioning
confidence: 99%